2010
DOI: 10.1029/2009wr008595
|View full text |Cite
|
Sign up to set email alerts
|

Simulating field‐scale moisture flow using a combined power‐averaging and tensorial connectivity‐tortuosity approach

Abstract: [1] Various methods have been developed over the past 3 decades to estimate effective unsaturated hydraulic properties. We developed an alternative practical approach to estimate three-dimensional effective unsaturated hydraulic conductivity via a combined power-averaging and tensorial connectivity-tortuosity (PA-TCT) model. An application of the PA-TCT model to data collected at a field injection site suggests that the model provides a reasonable framework for upscaling core-scale measurements as well as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…They found that there was evidence of saturation-dependent anisotropy and the anisotropy could be adequately described using the TCT model. Zhang and Khaleel (2010) developed a practical approach to estimate the 3D effective unsaturated hydraulic conductivity via a combined power-averaging and tensorial connectivity-tortuosity (PA-TCT) model. An application of the PA-TCT model to data collected at the Sisson and Lu site in the Hanford 6.6 200 East Area suggests that the model provides a reasonable framework for upscaling core-scale measurements as well as an accurate simulation of moisture flow in a heterogeneous vadose zone.…”
Section: The Stochastic (Polmann 1990) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that there was evidence of saturation-dependent anisotropy and the anisotropy could be adequately described using the TCT model. Zhang and Khaleel (2010) developed a practical approach to estimate the 3D effective unsaturated hydraulic conductivity via a combined power-averaging and tensorial connectivity-tortuosity (PA-TCT) model. An application of the PA-TCT model to data collected at the Sisson and Lu site in the Hanford 6.6 200 East Area suggests that the model provides a reasonable framework for upscaling core-scale measurements as well as an accurate simulation of moisture flow in a heterogeneous vadose zone.…”
Section: The Stochastic (Polmann 1990) Modelmentioning
confidence: 99%
“…Even for an anisotropic soil, some properties (e.g., porosity) are isotropic, while others (e.g., hydraulic conductivity) is anisotropic. Because there were no data to determine the degree of soil stratification at Hanford, Zhang and Khaleel (2010) quantified the levels of anisotropy in K based on the use of typical power law values (p) to estimate the upscaled unsaturated K in the horizontal (K h ) and vertical (K v ) directions for the different matrix anisotropy categories. The definitions apply to the whole range of saturation and are:  isotropic (ISO): p = 0, for both K h and K v  low anisotropy (LA) of matrix: p = 1 for K h and p = 1 / 3 for K v  intermediate anisotropy (IA) of matrix: p = 1 for K h and p = 0 for K v  high anisotropy (HA) of matrix: p = 1 for K h and p = -1 for K v Note that the above calculation is equivalent to the arithmetic mean when p = 1, the geometric mean when p = 0, and the harmonic mean when p = -1.…”
Section: Soil Anisotropy At Hanfordmentioning
confidence: 99%
“…Simulations were performed using baseline values of K s shown in Table 3.1 for the vertical direction, but increasing the K s values applied to the x-and y-directions by a factor of four (4X) for the H1, H2, and H3 subunits. In addition to anisotropy in K s , the combined effects of anisotropy in K s plus anisotropy in unsaturated hydraulic conductivity were evaluated using a tensorial connectivity-tortuosity (TCT) model (Zhang and Khaleel 2010;Rockhold et al 2015). The TCT model parameters that were used are listed in Table 3.1.…”
Section: Hydraulic and Sorption Parametersmentioning
confidence: 99%
“…Note that some of the spikes in flux-averaged concentrations shown previously for Tc-99 in Figure 4.11 are modulated or smoothed in Figure 4.12 as a result of lateral spreading of the simulated plumes. This is especially evident for Model_03, which includes anisotropy in K s as well as anisotropy in unsaturated hydraulic conductivity generated using the TCT model (Zhang and Khaleel 2010;Rockhold et al 2015). Table 3.1) were used as baseline parameters for these and subsequent simulations.…”
Section: 12mentioning
confidence: 99%
“…For example, the traditional ADE model predicts that the dispersivity is constant and that the first two moments of the contaminant plume both increase linearly with time (Bear, 1975). However, many simulations and experiments indicate that the dispersion coefficient increases with time and approaches an asymptotic value (Gelhar et al, 1992; Pickens and Grisak, 1981; Tompson, 1988; Zhang and Khaleel, 2010; Zhang et al, 2004). Besides, the first and second moments of the contaminant plume grow nonlinearly with time (Adams and Gelhar, 1992).…”
mentioning
confidence: 99%